Diagnostic Imaging of Ophthalmology A Practical Atlas (Springer Netherlands, 2018)
This atlas is a pocket manual of orbital diagnostic imaging. It includes common imaging techniques, normal imaging features, abnormal orbital imaging of developmental diseases, injury, inflammation, lymphoproliferative diseases, diseases of the eyeball, post-operative changes, vascular diseases, tumors and neuro-ophthalmological diseases. While it particularly focuses on CT and MRI, it also describes other techniques, such as X-ray, ultrasonography and nuclear imaging. The book starts with an overview of commonly used orbit imaging techniques and a concise description of imaging features of normal orbit in X-ray, CT and MRI. The following nine chapters explore different orbital diseases and abnormalities that are common in clinical work. It is a valuable resource for radiologists and ophthalmologists.